Prognostic factors for hematotoxicity of chemotherapy in aggressive non-Hodgkin's lymphoma. - Ziepert, M.; Schmits, R.; Trumper, L.; Pfreundschuh, M.; Loeffler, M. (Ann Oncol, 2008)
BACKGROUND: Little is known on the heterogeneity of hematotoxicity in patients receiving multicycle chemotherapy. PATIENTS AND METHODS: We analyzed data of 1399 patients with aggressive lymphoma from trials using CHOP (combination chemotherapy with cyclophosphamide, doxorubicin, vincristine and prednisone)-like therapies. Multivariate modeling was carried out for leukocytopenia, thrombocytopenia and anemia and the models were validated by two large independent datasets from trials with/without usage of the CD20-antibody rituximab. RESULTS: On the basis of these models, we are able to predict the remarkable heterogeneity of hematotoxicity and propose to use risk groups. Regarding leukocytopenia, the low toxicity risk group experienced World Health Organization grade 4 in <10% of the cycles while the high toxicity risk group in almost all cycles. For thrombocytopenia, groups were detectable with almost no grade 3 or 4 toxicity and others where two out of three cycles were affected. In a separate set of models, the first cycle toxicity was the strongest predictor for later hematotoxicity. The risk for leukocytopenia was associated with infections, antibiotic use, hospitalization and treatment-related mortality, indicating the clinical usefulness of the models. For the first time, a Web-based tool is made available to easily predict the hematotoxicity in clinical practice (www.toxcalculator.com). CONCLUSION: This analysis has implications for patient management and prophylaxis.
Keywords: Adult; Aged; Antineoplastic Combined Chemotherapy Protocols/administration & dosage/*adverse effects/therapeutic use; Clinical Trials as Topic; Cyclophosphamide/administration & dosage/adverse effects; Doxorubicin/administration & dosage/adverse effects; Female; Germany; Hematologic Diseases/*chemically induced; Hospitalization/statistics & numerical data; Humans; Infections/drug therapy/etiology/mortality; Leukopenia/chemically induced; Lymphoma, Non-Hodgkin/*drug therapy/pathology; Male; Middle Aged; Models, Statistical; Multicenter Studies as Topic; Multivariate Analysis; Odds Ratio; Predictive Value of Tests; Prednisone/administration & dosage/adverse effects; Prognosis; Risk Assessment; Risk Factors; Thrombocytopenia/chemically induced; Vincristine/administration & dosage/adverse effects